Chair yoga for strength & balance : accessible exercises to improve mobility & relieve pain - Maitreyi, M. L. (Cider Mill Press Book Publishers, 2025)
"Whether due to aging, long hours at a desk, or recovery from injury, limited mobility can feel both painful and frustrating. But what if the solution were right beneath you? Transform your daily sitting time into an opportunity for strength, healing, and natural movement. Chair Yoga for Core Strength & Balance offers a gentle, immediate way to rebuild mobility--using the chair you're already sitting in. Perfect for seniors, office professionals, beginners, and anyone with limited movement. No prior yoga experience needed" --